2020
DOI: 10.1038/s41598-020-59320-9
|View full text |Cite
|
Sign up to set email alerts
|

Trait-Based Comparison of Coral and Sponge Microbiomes

Abstract: corals and sponges harbor diverse microbial communities that are integral to the functioning of the host. While the taxonomic diversity of their microbiomes has been well-established for corals and sponges, their functional roles are less well-understood. It is unclear if the similarities of symbiosis in an invertebrate host would result in functionally similar microbiomes, or if differences in host phylogeny and environmentally driven microhabitats within each host would shape functionally distinct communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 132 publications
4
9
0
Order By: Relevance
“…Although they were from the same site, it is unknown whether the two snail species occupied identical microhabitats. Subtle differences in microhabitats may be reflected in the significant differences in low-abundance groups and functions (Fiore et al 2020). Finally, our results indicated that Firmicutes were the major component of viviparid gut flora.…”
Section: Discussionmentioning
confidence: 56%
“…Although they were from the same site, it is unknown whether the two snail species occupied identical microhabitats. Subtle differences in microhabitats may be reflected in the significant differences in low-abundance groups and functions (Fiore et al 2020). Finally, our results indicated that Firmicutes were the major component of viviparid gut flora.…”
Section: Discussionmentioning
confidence: 56%
“…Parasitic infection appears to perturb microbiome composition, and our data predict shifts in the timings of peak biosynthetic, degradative and energy generation pathway activity in the microbial community. Understanding of the functional importance to the host of commensal microbiota in teleost skin is still in its infancy [ 52 ], and 16S rRNA predictive functional analyses are only indicative of actual microbial activity [ 61 ]. However, we also find strongly contrasting taxonomic and functional profiles between the two timepoints used for full-scale metagenomic analysis, which further supports daily cycles in microbiome composition and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic infection appears to perturb microbiome composition, and shift the timings of peak biosynthetic, degradative and energy generation pathway activity in the microbial community. Understanding of the functional importance to the host of commensal microbiota in teleost skin is still in its infancy 48 , and predictive metagenomic analyses are only indicative of actual microbial activity 57 . Temporal metatranscriptomic profiling will be an important means to build upon our results to decipher the functional significance of teleost mucosal microbiota and their daily coordination of activity.…”
Section: Discussionmentioning
confidence: 99%